Nutritional and cooking properties of some rice varieties in Noakhali region of Bangladesh - Anjum, Kazi Ishrat; Hossain, Mohammad Anowar (Research in Agriculture Livestock and Fisheries, 2019)
The experiment was conducted to evaluate the nutritional and cooking properties of some rice varieties collected from the farmers of Noakhali region of Bangladesh. Noakhali district is situated in the coastal belt of the country and this area also termed as ‘char’ land. All of the selected varieties were grown in saline soil condition. For assessment of nutritional quality, protein, iron and zinc content were estimated. The protein, iron and zinc content ranged from 6.75 to 8.63%, 7.09 to 9.84ppm, 24.52 to 32.34ppm, respectively. The highest amount of protein, iron and zinc were found in Kajalshail variety. All of the rice varieties showed significant variation for all cooking properties studied in this work. The volume expansion ratio (VER) was varied from 1.89 to 2.20. The kernel elongation ratio (KER) was greater than 1.1 in all varieties except Carandol. On cooking Kajalshail variety exhibited highest VER and KER 2.20 and 1.19, respectively. Based on the gel consistency (GC) test, the average GC values ranged from 39.73 to 92.53mm and varieties were categorized as hard, medium and soft. On the basis of alkali spreading value (ASV) the varieties were classified into three groups namely- low, intermediate and high. ASV was found significantly and negatively correlated with gelatinization temperature (GT). The Kajalshail variety was found to have the better nutritional and cooking quality among all varieties. Res. Agric., Livest. Fish.6(2): 235-243, August 2019